Contemporary marketing - Boone, Louis E. (Thomson South-Western, 2006)
CONTEMPORARY MARKETING by Boone and Kurtz has proven to be the premier principles of marketing text and package since the first edition. With each edition, this best selling author team builds and improves upon past innovations, creating the most technologically advanced, student friendly, instructor supported text available. The twelfth edition continues to provide the most current and up-to-date content by including the most current coverage of topics such as one-to-one marketing, strategic planning, guerilla marketing, customer relationship management, and much more